2019
DOI: 10.1155/2019/8630504
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Intralenticular Injection of Ozurdex® for Branch Retinal Vein Occlusion: Intact Posterior Capsule and Resolution of Macular Edema

Abstract: Purpose. We present a case of accidental intralenticular injection of Ozurdex implant in a patient with macular edema secondary to branch retinal vein occlusion. Method. A case report. Results. Intravitreal dexamethasone implant injection had been performed for macular edema due to left superior temporal vein branch occlusion to the left eye of a 78-year-old male patient. The slit-lamp examination 85 days later revealed that the dexamethasone implant was intralenticular. The best-corrected visual acuity (BCVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Occasionally, it is possible to leave Ozurdex in the crystalline lens intact [8]. In some cases, if the posterior capsule is undamaged, it is possible to leave Ozurdex intralenticular intact, and remove it within a period of 85 days after injection [5]. In our opinion, there is a need to perform phacoemulsification as soon as possible.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Occasionally, it is possible to leave Ozurdex in the crystalline lens intact [8]. In some cases, if the posterior capsule is undamaged, it is possible to leave Ozurdex intralenticular intact, and remove it within a period of 85 days after injection [5]. In our opinion, there is a need to perform phacoemulsification as soon as possible.…”
Section: Discussionmentioning
confidence: 93%
“…However, repositioning of the implant into Berger's space resulted in a favorable therapeutic effect with a good anti-inflammatory and anti-edema response. Some authors have described the efficacy of Ozurdex even in cases with its intralenticular position [5].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the right eye (without Ozurdex injection) had persistent uveitis and the left eye (with Ozurdex injection) had no uveitis, indicating that intralenticular Ozurdex was still effective for uveitis and the effect duration of intralenticular Ozurdex was much longer than normal (4–6 months). A previous study indicated that, after the discovery of intralenticular injection of Ozurdex, immediate cataract surgery might increase the posterior capsule stress and tear the posterior capsule [ 23 ]. When we chose the wait-and-see strategy, the posterior capsule rupture might become fibrosed and recover during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The development of cataract may take as long as 10-12 months after injection [2,3,13]. Some authors [2,3,5,14,15] have found resolution of the macular edema with an intralenticular implant. Coca-Robinot et al [12] and Baskan et al [4] found no significant macular edema improvement.…”
Section: Basu and Jhamentioning
confidence: 99%